Statistic Analysis The Ability To Use Mind Mapping In Descriptive Writing At Junior High School - Serly Maulina Syaif; Suhartawan Budianto; Kusuma Wijaya (PT. Gudang Pustaka Cendekia, 2025)
This study exemines the ability to use mind mapping in descriptive writing in grade eight junior high school. This study uses quantitative methods by dividing into two groups, namely the experimental group and the control group. The experimental group is taught using mind mapping and the control group taught with the classical method. Data analysis is calculated using the t-test formula. The result showed that mind mapping method is effective in descriptive text writing. It can be proven in the result of the value of t = -4.982 with p-value = 0.000. So, it can be concluded that H₀ is rejected and H₁ is accepted. So, the use of mind mapping method is effective to help students think more creatively in descriptive writing.